2020
DOI: 10.1007/s10916-020-01550-5
|View full text |Cite
|
Sign up to set email alerts
|

VR4Health: Personalized teaching and learning anatomy using VR

Abstract: Virtual Reality (VR) is being integrated into many different areas of our lives, from industrial engineering to video-games, and also including teaching and education. We have several examples where VR has been used to engage students and facilitate their 3D spatial understanding, but can VR help also teachers? What are the benefits teachers can obtain on using VR applications? In this paper we present an application (VR4Health) designed to allow students to directly inspect 3D models of several human organs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
0
20
0
4
Order By: Relevance
“…It widens accessibility to learning opportunities and brings improved motivation and engagement through the new things to be learned. Of course, these new experiences will not be the same as previous ones, but it has been facilitating students’ learning process ( Fairén et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It widens accessibility to learning opportunities and brings improved motivation and engagement through the new things to be learned. Of course, these new experiences will not be the same as previous ones, but it has been facilitating students’ learning process ( Fairén et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, these new experiences will not be the same as previous ones, but applications such as (VR4Health, _cublens, Switzerland) have been shown to facilitate students' learning of the various anatomical structures and their relationships with one another. 4 Feedback from teachers is invaluable, but can be achieved with the use of online video communication services in which the teacher can utilise screen-sharing options to walk students through anatomy on any online forum. Some schools already include virtual anatomy in their courses, but current needs must be met by adapting and collaborating as a whole to optimise our medical education broadly.…”
Section: The Completion Of Telehealth Interactions That Are Supplemenmentioning
confidence: 99%
“…Johnston et al [24] claim that VR models involving 3D images allow students to interact with "real" microscopic models, resulting in a significant increase in the understanding of processes. On the other hand, Fairén, Motés and Insa [25] found that the most important added value of using VR in a science course is that students adapt the activity to their academic needs, allowing the equipment to be used as a self-management tool.…”
Section: Vr Chemistry Educationmentioning
confidence: 99%